NRASQ61R Mutation-specific Immunohistochemistry Also Identifies the HRASQ61R Mutation in Medullary Thyroid Cancer and May Have a Role in Triaging Genetic Testing for MEN2. (January 2017) - Reagh, Jessica; Bullock, Martyn; Andrici, Juliana; Turchini, John; Sioson, Loretta; Clarkson, Adele; Watson, Nicole; Sheen, Amy; Lim, Grace; Delbridge, Leigh; Sidhu, Stan; Sywak, Mark; et al.
Abstract : A quarter of patients with medullary thyroid carcinoma (MTC) have germline mutations in the RET proto-oncogene indicating MEN2. Therefore genetic testing is recommended for all patients presenting with MTC. Approximately 40% of MTCs have somatic RET mutations. Somatic mutations in the RAS genes are the next most common driver mutations and appear to be mutually exclusive with germline RET mutation. The single most common somatic RAS mutation is HRASQ61R (c.182A>G), reported in 4.6% to 11% of all MTCs. Mutation-specific immunohistochemistry (IHC) initially developed to identify the NRASQ61R mutation in melanoma (clone SP174) has proven highly sensitive and specific. Because the amino acid sequences for the HRAS and NRAS proteins at codon 61 are identical, we postulated that SP174 IHC would also identify the somatic HRASQ61R mutation. IHC with SP174 was performed on a tissue microarray of 68 patients with MTC including 13 (22.8%) with molecularly confirmed MEN2. Seven (10.3%) MTCs demonstrated positive staining. Six of these patients had already undergone germline RET mutation testing as part of clinical care and were all confirmed to be wild type, excluding the diagnosis of MEN2. All SP174 immunohistochemically positive MTCs were proven to have HRASQ61R mutation (and lack KRASQ61R and NRASQ61R) by Sanger sequencing. All MEN2 patients showed negative staining. We conclude that IHC with SP174 is highly specific for the HRASQ61R mutation in MTC. Because current data suggest that this mutation is mutually exclusive with germline RET mutation, IHC may also have a role in triaging formal genetic testing for MEN2.